2006
DOI: 10.1002/jez.a.350
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen metabolism and excretion in the aquatic chinese soft-shelled turtle,Pelodiscus sinensis, exposed to a progressive increase in ambient salinity

Abstract: This study aimed to determine effects of 6-day progressive increase in salinity from 1 per thousand to 15 per thousand on nitrogen metabolism and excretion in the soft-shelled turtle, Pelodiscus sinensis. For turtles exposed to 15 per thousand water on day 6, the plasma osmolality and concentrations of Na+, Cl- and urea increased significantly, which presumably decreased the osmotic loss of water. Simultaneously, there were significant increases in contents of urea, certain free amino acids (FAAs) and water-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 33 publications
3
27
1
Order By: Relevance
“…These results are in agreement of studies by other researchers (Gibbons et al,1979;Shu et al, 2012 (Minnich, 1979), P. sinensis, 285 mOsm/kg (Lee et al, 2006). Our results for T. s. elegans are similar, with individuals maintaining a plasma osmolarity of 250-261 mOsm/kg.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement of studies by other researchers (Gibbons et al,1979;Shu et al, 2012 (Minnich, 1979), P. sinensis, 285 mOsm/kg (Lee et al, 2006). Our results for T. s. elegans are similar, with individuals maintaining a plasma osmolarity of 250-261 mOsm/kg.…”
Section: Discussionsupporting
confidence: 93%
“…And the other is maybe the increase in the rate of urea synthesis. Lee et al (2006) studied that increases in urea contents in tissues of P. sinensis on days 3, 4 and 6 indicated an increase in the rate of urea synthesis, and the overall rate of urea synthesis increased 1.4 fold during the 6 d. Also, the capacity of P. sinensis to retain urea is apparently limited, and the urea excretion rate returned back to the control level as the plasma urea concentration increased, which is coincident with our results. However, the recent study on an important excretory route for urea in P. sinensis has shown that it is well adapted to aquatic environments, including brackish swamps and marshes, can excrete urea mainly through the buccophyaryngeal cavity of mouth instead of the kidney during immersion (Ip et al, 2012).…”
Section: Increase In Urea Contents In Response To Increasedsupporting
confidence: 88%
“…While the osmotic environment of obligate marine species remains relatively stable, estuarine species may encounter fluctuations in salinity due to tidal influences and freshwater availability. Several reptilian species take advantage of the temporal availability of resources in estuaries (Dunson, 1970;Dunson, 1980;Dunson, 1986;Ellis, 1981;Taplin et al, 1982;Mazzotti et al, 1986;Lillywhite and Ellis, 1994;Leslie and Spotila, 2000;Lee et al, 2006), but there are very few that live entirely within the estuarine habitat. Of the estuarine turtles, the diamondback terrapin, Malaclemys terrapin (Schwartz 1955), is the only species endemic to estuarine habitats in the temperate zone (Hart and Lee, 2006;Rasmussen et al, 2011), and can tolerate brackish to hypersaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It may be partially or completely exposed to air when the ponds or creeks dry up during hot spells or when it emerges from waters to bask. Pelodiscus sinensis is ureogenic and possesses a full complement of ornithine-urea cycle (OUC) enzymes in its liver (Lee et al, 2006;Lee et al, 2007). It is primarily ureotelic, excreting the majority (71%) of the waste nitrogen (N) as urea-N in freshwater.…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to brackish water (salinity 15), significant increases in plasma osmolality, [Na + ], [Cl -] and [urea], which presumably decrease the osmotic loss of water, occur in P. sinensis (Lee et al, 2006). Simultaneously, there are significant increases in concentrations of urea, certain free amino acids (FAAs) and water-soluble proteins in various tissues, presumably for cell volume regulation.…”
Section: Introductionmentioning
confidence: 99%